Education Policy and the Regional Distribution of Schools - Teshome, Mulat (The Ethiopian Journal of Education, 2024)
The development of educational policy is reviewed in the light of the observed rapid growth in the provision of educational services and the recent establishment of offices for regional planning and development. The paper also identifies and measures the important factors affecting the regional distrbution of schools.